Continuous-flow microwave thermal processing of cloudy apple juice. - Siguemoto, Érica Sayuri (2018)
Continuous-flow microwave heating is an alternative processing technology that can bring advantages to the pasteurization of food products, particularly, fruit-based beverages. This work aimed to study the continuous-flow microwave thermal processing of cloudy apple juice. Dielectric and electric properties of cloudy apple juices, obtained from different varieties and from an industrial plant, were determined from 500 to 3000 MHz and temperatures between 10 °C and 90 °C. At these frequencies, apple variety showed little influence and the permittivity decreased almost linearly with temperature. Inactivation kinetics of pathogen microorganisms (Escherichia coli O157:H7 and Listeria monocytogenes) and enzymes (polyphenol oxidase, peroxidase and pectin methylesterase) were studied and modeled to evaluate non-thermal effects of microwave radiation. For both processing technologies, it was possible to achieve a 5-log10 reduction of E. coli and L. monocytogenes, as recommended by the FDA. Microwave processing in comparison to conventional heating enhanced the microorganism inactivation in 18 out of 28 experiments. Predicted enzyme inactivation curves for pasteurization at 70 °C and 80 °C of the cloudy apple juice showed that pectin methylesterase has the highest thermal resistance and that there was no significant evidence of non-thermal microwave effects. A pilot scale unit used for pasteurizing fruit juices was evaluated and the process was modeled and simulated to determine the average time-temperature history. Mean residence times and dispersion parameters were obtained from internal volume measurements and residence time distribution experiments. Thermal processing experiments using water provided heat transfer coefficients as functions of Reynolds number and also microwave power absorption. Mathematical modeling was used to determine the temperature distribution along the product path and results were validated. Results showed that focused microwave heating provided the necessary temperature increase in a very short time, with a lethality contribution of only 0.7% as compared to 59-68% when using the conventional heat exchanger, which configures over-processing and can decrease product quality. Fresh cloudy apple juice was subjected to continuous flow microwave assisted pasteurization in a pilot scale unit at three processing temperatures (70 °C, 80 °C and 90 °C), two flow rate levels and two heating systems (conventional and focused microwave). Good results were obtained for polyphenol oxidase and peroxidase inactivation, but not for pectin methylesterase, which showed to be the most resistant enzyme. A comparative evaluation on quality changes was performed in cloudy apple juice samples pasteurized in the continuous-flow unit. Profile of volatiles of the microwave pasteurized apple juice was more similar to the nonpasteurized juice, in comparison with the conventionally pasteurized juice. However, total organic acids and total soluble sugar contents were not significantly different between both processing technologies. There was an increase of phenolic contents during processing of cloudy apple juice, possibly due to the extraction of phenolic compounds present in suspension of material. Furthermore, it was observed the same trend of antioxidant capacity by DPPH and ORAC methods. In conclusion, this PhD work presents the potential of the microwave-assisted pasteurization in cloudy apple juice regarding enzymatic, microbiological and quality aspects.